2015
DOI: 10.1016/j.bpg.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Barrett's oesophagus (clinical): LOS dysfunction, hiatal hernia, peristaltic defects

Abstract: Summary Barrett’s esophagus, with the potential to develop into esophageal adenocarcinoma (EAC), is a major complication of gastroesophageal reflux disease (GERD). However, about 50% of patients developing EAC had no known GERD beforehand. Hence, while GERD symptoms, esophagitis, and Barrett’s have a number of common determinants (esophagogastric junction (EGJ) incompetence, impaired esophageal clearance mechanisms, hiatus hernia) they also have some independent determinants. Further, although excess esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…7,18 The presence of hiatal hernia is highly prevalent among patients with BE (up to 96.0%). 19 The close relationship between hiatal hernia and BE has been previously described in the literature as well as the correlation between LSBE and hiatal hernia length. A meta-analysis has shown that the presence of hiatal hernia is associated with an increased risk of developing BE (OR, 3.94; 95% CI, 3.02-3.96).…”
Section: Discussionmentioning
confidence: 62%
“…7,18 The presence of hiatal hernia is highly prevalent among patients with BE (up to 96.0%). 19 The close relationship between hiatal hernia and BE has been previously described in the literature as well as the correlation between LSBE and hiatal hernia length. A meta-analysis has shown that the presence of hiatal hernia is associated with an increased risk of developing BE (OR, 3.94; 95% CI, 3.02-3.96).…”
Section: Discussionmentioning
confidence: 62%
“…However, unlike oesophageal adenocarcinomas, these cardia and junctional cancers have only a very weak association with a previous history of reflux symptoms 7 8. These observations suggest that the mechanism of acid exposure inducing these junctional cancers may be different from traditional transsphincteric reflux 9 10…”
Section: Introductionmentioning
confidence: 96%
“…Prokinetic drugs are not recommended in guidelines neither as monotherapy nor as add-on treatment as there is no evidence supporting their efficacy in the treatment of hiatal hernia associated with GERD [20,23].…”
Section: Treatment Of Hiatal Herniamentioning
confidence: 99%